The Hindu householder the T.N. Madan omnibus - Madan, T. N. (Oxford : Oxford University Press, 2010)
Focusing on the householder in Hindu society, this Omnibus brings together distinguished sociologist T.N. Madan's writings on the theme. With a new preface, prologue, epilogue, and three new appendices, the omnibus sheds light on life and society of Pandits in the Kashmir Valley.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Households -- India -- Jammu and Kashmir; Kashmiri Pandits; Families -- India -- Jammu and Kashmir; Jammu and Kashmir (India) -- Social life and customs; Jammu and Kashmir (India) -- Social conditions